Uria lomvia (Alcidae) - Landung am Brutfelsen - Georg Rüppell (IWF (Göttingen), 1969)
(en)The film shows the landing procedure of the guillemot Uria lomvia. A shooting speed of 64 f/s permits a breakdown of the sequence of movements. Approach path and changes in wing movements during landing are demonstrated, and take-off from water and from the cliff face are also included.